Use of Transversus Abdominis Plane and Intercostal Blocks in Bitches Undergoing Laparoscopic Ovariectomy: A Randomized Controlled Trial - Andrea Paolini; Francesco Santoro; Amanda Bianchi; Francesco Collivignarelli; Massimo Vignoli; Silvia Scialanca; Salvatore Parrillo; Ilaria Falerno; Andrea De Bonis; Martina Rosto; Roberto Tamburro (Veterinary Sciences, 2022)
In humans and dogs, loco-regional anesthesia is associated with lower peri-operative opioid consumption and less related side effects. The combination of transversus abdominis plane (TAP) and intercostal blocks can be used to desensitize the entire abdominal wall in dogs. The aim of this study was to evaluate the effectiveness of TAP and intercostal blocks in bitches undergoing laparoscopic ovariectomy. Twenty client-owned bitches were enrolled in this double-blinded randomized controlled trial. After premedication with dexmedetomidine, methadone and ketamine, the animals were randomized into two groups. Dogs in the TAP group received intercostal blocks from T8 to T10 and a TAP block with ropivacaine. Dogs in the FEN group received a fentanyl bolus and a constant rate infusion for the entire duration of the procedure. Intra-operative cardiovascular stability, post-operative pain scores, rescue opioid requirement, dysphoria during recovery, time to attain sternal recumbency and interest in food at 6 h post-extubation were compared. Bitches in the TAP group received a statistically significant lower amount of rescue fentanyl intra-operatively and methadone post-operatively. Pain scores were lower in the TAP group until 6 h post-extubation. No difference was found for dysphoric recoveries, time to attain sternal recumbency and appetite at 6 h post-extubation. No adverse event was recorded for any of the dogs. The combination of TAP and intercostal blocks can be part of an effective multi-modal analgesic strategy in bitches undergoing laparoscopic ovariectomy.